Chinese floating migrants: Rural-urban migrant labourers' intentions to stay or return. (February 2017) - Mohabir, Nalini; Jiang, Yanpeng; Ma, Renfeng
Abstract: The movement from rural areas and agricultural economies to urban spaces has been the most significant migration trend shaping Chinese society. Rural migrants moving to urbanized areas serve as a floating labour pool, providing flexible and cheap labour for urbanization and industrialization processes (increasingly over the past three decades). During periods of slow economic development, however, there is a pattern of return migration from the urban back to the rural. Over the last decade, older rural migrants, or first-generation migrants, tend to return to their home villages periodically, during times of economic downturn, but this does not imply that migration to cities has decreased. Younger people from rural villages continue to migrate to the city in search of urban economic opportunities and to escape rural poverty, regardless. The purpose of this paper, then, is to explore the intentions and context of floating migrants' decisions to return "home" or to remain in the city. This research examines how notions of gender, age and sense of belonging affect the choice of rural migrants to stay or return, including different calculations in the decision-making process across age and gender. The question of whether to stay or return is framed through the lens of belonging, which allows us to explore the changing priorities of a younger generation of floating migrants. Based on fieldwork in Shanghai and Anhui, we find that the floating workers interviewed prefer to remain in mega-cities as opposed to smaller cities or returning home to rural areas. The findings contextualize the residential dilemmas facing floating migrants, and points to different factors across age in deciding whether to stay in the city, or return to the village during economic slumps. Highlights: The current economic downturn in China suggests older floating migrants are under greater pressure to return to their villages, but despite hardships younger floating migrants choose to remain in large urban centres. China's central government has undertaken harsh push/pull measures to control urbanization in mega-cities. New Type Urbanization planning needs to take into account individual motivations rather than simply housing supply.